Contributions of Sokoto State Government In Funding Adult And Non-Formal Education Programmes In Sokoto State, Nigeria - Murtala Akanbi Yusuf; Lawali Aliyu Filasko; Muhammad Mustapha Jagaba (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2020)
This study assessed the contributions of Sokoto State government in funding Adult and Non-Formal Education Programmes in the State within a period of 10 years from 2008 to 2017. Descriptive survey research design was used in the study. The population of the study comprised 14 principal officers from the State Agency for Mass Education, Sokoto and the same total number were used for the final analysis. The sampled agency is State Agency for Mass Education, Sokoto. Data collected through records and questionnaire were analysed using descriptive statistics such as tables, frequencies and percentages as well as charts. The study showed that Adult and Non-Formal Education Programmes in Sokoto State suffer from deficits funding and improper financial records keeping which hampers the progress and effective performance of the State Agency for Mass Education, Sokoto in running Adult and Non-Formal Education Programmes in the State. In line with the findings the study recommends that Sokoto State Government through the State Ministry of Basic and Secondary Education should increase its budgetary allocations to Adult and Non-Formal Education Programmes from the annual allocation budget given to educational sector. Additionally, proper record and updated financial record keeping should be documented by the State Agency for Mass Education, Sokoto.